2016
DOI: 10.1177/0885066614544452
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dexmedetomidine Versus Propofol on Hospital Costs and Length of Stay

Abstract: In this academic medical center, dexmedetomidine use was associated with higher costs when compared to propofol for sedation in the ICU. Also, use of dexmedetomidine was associated with increased lengths of ICU and hospital stay. Future prospective trials are needed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…18,24,33 Previous cost studies have demonstrated that clinical outcomes associated with sedative choice can impact the overall cost of an ICU stay. 18,24,30,[33][34][35][36][37] The drivers of cost savings in this analysis were also consistent with previous studies, with the key driver of high costs being the fixed room and board costs associated with the ICU stay. 18,24,33,37 The absolute costs and the magnitude of the cost differences, however, differed between our analysis and previous cost studies which included mixed patient populations requiring both long-term and short-term sedation.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…18,24,33 Previous cost studies have demonstrated that clinical outcomes associated with sedative choice can impact the overall cost of an ICU stay. 18,24,30,[33][34][35][36][37] The drivers of cost savings in this analysis were also consistent with previous studies, with the key driver of high costs being the fixed room and board costs associated with the ICU stay. 18,24,33,37 The absolute costs and the magnitude of the cost differences, however, differed between our analysis and previous cost studies which included mixed patient populations requiring both long-term and short-term sedation.…”
Section: Discussionsupporting
confidence: 88%
“…In that analysis, total hospital costs when ICU patients were treated with dexmedetomidine were $46,716 compared to $31,041 in the propofol group. 37 However, the increased LOS that drove the cost differential was not adjusted for potential unmeasured confounders, such as dosing, level of sedation, delirium screening, or rescue sedation. Additionally, there were several observed differences between the two patient populations (eg, age, sex, race, admission type, service category, and severity of illness) that may suggest selection bias for treatment with each sedative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results found that there was no significant difference between the 2 groups in terms of the length of hospital stay. Patanwala et al [24] found that use of dexmedetomidine was associated with increased lengths of ICU and hospital stay. However, this was a retrospective study and author also stated that future prospective trials are needed to confirm their conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…When compared with propofol for sedation in the ICU, dexmedetomidine may increase the length of hospital stay. [24] Obviously, prolonged length of hospital stay may increase the economic costs for the patients. Ren et al [19] found that administration of dexmedetomidine could significantly decrease the length of hospital stay when compared with the control group.…”
Section: Discussionmentioning
confidence: 99%